English in Local Newspaper: Will It Ruin Bahasa Indonesia? - Aisyah Hamidiyah (Universitas Bunda Mulia, 2017)
A language can be globally spread out to whole parts of an area in the world by the power of media. Media helps English to be globally accepted by the people in the world. New terms related with technology and innovation are usually written in English and inserted in the articles and news. Radar Banten is a local newspaper in Serang written in Bahasa Indonesia. It inserts English in one of its articles. The article is written for readers in their teens. What kinds of words inserted in the article, the categories of English words, and the effect of inserting the words will be discussed in the paper. Keywords: English, local newspaper, bahasa Indonesia